Vocal and Electric Fish: Revisiting a Comparison of Two Teleost Models in the Neuroethology of Social Behavior - Dunlap, Kent D.; Koukos, Haley M.; Chagnaud, Boris P.; Zakon, Harold H.; Bass, Andrew H. (Frontiers in Neural Circuits, 2021)
The communication behaviors of vocal fish and electric fish are among the vertebrate social behaviors best understood at the level of neural circuits. Both forms of signaling rely on midbrain inputs to hindbrain pattern generators that activate peripheral effectors (sonic muscles and electrocytes) to produce pulsatile signals that are modulated by frequency/repetition rate, amplitude and call duration. To generate signals that vary by sex, male phenotype and social context, these circuits are responsive to a wide range of hormones and neuromodulators acting on different timescales at multiple loci. In 2005, Bass and Zakon (2005) reviewed the behavioral neuroendocrinology of these two teleost groups, comparing how the regulation of their communication systems have both converged and diverged during their parallel evolution. Here, we revisit this comparison and review the complementary developments over the past 16 years. We a) summarize recent work that expands our knowledge of the neural circuits underlying these two communication systems, b) review parallel studies on the action of neuromodulators (e.g., serotonin, AVT, melatonin), brain steroidogenesis (via aromatase), and social stimuli on the output of these circuits, c) highlight recent transcriptomic studies that illustrate how contemporary molecular methods have elucidated the genetic regulation of social behavior in these fish, and d) describe recent studies of mochokid catfish that use both vocal and electric communication and consider how these two systems are spliced together in the same species. Finally, we offer avenues for future research to probe how similarities and differences emerge during ontogeny and evolution.